Effect of Strengthening Family Coping Resources on Emotion Regulation of Family Caregivers of Patients with Schizophrenia - Somaye Kazemian; Narges Zarei; Masoume Esmaeily (Mashhad University of Medical Sciences, 2020)
Background: Strengthening the coping resources as an instruction for anxiety-regulation may affect the emotion-regulation of families. Regarding the significant role of families in health of these patients, it seems that interference in strengthening coping resources affects their emotion-regulation. Aim: This study aimed to determine the effect of strengthening family coping resources on the emotion-regulation of schizophrenic patients' caregivers.   Method: This quasi-experimental research was conducted on families with hospitalized schizophrenic patients in one of the most prominent psychiatric centers in the Northeast of Iran in 2018. The participants were assigned to intervention (n=29) and control (n=31) groups. A short revised form of Emotion-Regulation Questionnaire was utilized as data collection tool. The intervention based on strengthening family coping resources (SFCR) was administered in three modules and 15 group sessions (groups of 6-8 individuals) according to the instructions of the multi-family model of Kisser et al. On the other hand, the controls received routine cares in hospital wards.The data were analyzed in SPSS software version (16) using independent and paired t-tests. Results: The groups were homogenous in terms of demographic characteristics. The result of independent t-test demonstrated a significant difference in the mean score of revaluation (P=0.001) and suppression (p=0.001) in the intervention group, compared to the control group, after the intervention. Implications for Practice: This intervention can guide clinicians on how to implement a family-centered care program to reduce the burden of caring schizophrenic patients through gaining family support in the efficient care of these patients.